On Some Problems of Strongly Ozaki Close-to-Convex Functions - Zahra Maleki; Saeid Shams; Ali Ebadian; Ebrahim Analouei Adegani (Journal of Function Spaces)
The purpose of the current paper is to investigate some geometric properties of the class FOν,γ, called strongly Ozaki close-to-convex functions, such as strongly starlikeness and close-to-convexity. Further, we find sharp bounds on Fekete-Szegö functionals and logarithmic coefficients for functions belonging to the class FOν,γ, which incorporates some known outcomes as the specific cases.